Board Composition and Corporate Social Responsibility: The Role of Diversity, Gender, Strategy and Decision Making - Rao, Kathyayini (Journal of business ethics, 2016)
This paper aims to critically review the existing literature on the relationship between corporate governance, in particular board diversity, and both corporate social responsibility (CSR) and corporate social responsibility reporting (CSRR) and to suggest some important avenues for future research in this field. Assuming that both CSR and CSRR are outcomes of boards’ decisions, this paper proposes that examining boards’ decision making processes with regard to CSR would provide more insight into the link between board diversity and CSR. Particularly, the paper stresses the importance of studies linking gender diversity and CSR decision making processes, which is quite rare in the existing literature. It also highlights the importance of more qualitative methods and longitudinal studies for the development of understanding of the diversity–CSR relationship.